2019
DOI: 10.1590/0104-1428.05818
|View full text |Cite
|
Sign up to set email alerts
|

Effects of miniemulsion operation conditions on the immobilization of BSA onto PMMA nanoparticles

Abstract: Polymer nanoparticles have been widely used in many biomedical applications, constituting a major incentive for immobilization of proteins. Poly(methyl methacrylate) nanoparticles were synthesized through miniemulsion polymerizations and used as supports for bovine serum albumin immobilization. Particularly, the effects of surfactant type (anionic sodium dodecyl sulfate and cationic cetyl trimethyl ammonium bromide) surfactant concentration and monomer holdup on some of the final nanoparticle properties (parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…As a matter of fact, it is well known in the field that the character of the surfactant can influence the kinetic behavior of miniemulsion polymerizations. [29,30,39] Campos et al (2019) [32] also observed that MMA polymerizations stabilized by SDS were less subject to inhibitory effects than MMA polymerizations stabilized by CTAB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, it is well known in the field that the character of the surfactant can influence the kinetic behavior of miniemulsion polymerizations. [29,30,39] Campos et al (2019) [32] also observed that MMA polymerizations stabilized by SDS were less subject to inhibitory effects than MMA polymerizations stabilized by CTAB.…”
Section: Resultsmentioning
confidence: 99%
“…The organic phase was prepared with 0-20 wt% of PZQ, 0-10 wt% of DEAEMA or DMAEMA, 10 wt% of mineral oil and 1 wt% of AIBN in MMA. These concentrations were defined in accordance with previous MMA miniemulsion polymerization [32] and PZQ encapsulating studies in PMMA nanoparticles, [2] PMMA microparticles [33] and MMA-based copolymer microparticles. [14,15] The initial miniemulsion was prepared through sonication with ice-bath, using a sonicator provided by Branson (Branson 450, Marshall Scintific, Hampton, USA) at 160 W for 5 min.…”
Section: Synthesis Of Polymer Nanoparticlesmentioning
confidence: 99%
“…These concentrations were defined in accordance with previous MMA miniemulsion polymerization studies. [8,16,29,30] The initial miniemulsions were prepared with a sonifier (Branson 450, Marshall Scintific, Hampton, USA) at 160 W for 5 min or with an ultra-turrax (T10 basic, IKA, Staufen, Germany) for 5 min at 14,500 rpm, using an ice bath to control the temperature of the emulsified system and keep it close to room temperature. The polymerizations were conducted in a 100 mL glass reactor (EasyMax 102, Mettler Toledo, Ohio, USA) at 80 o C under the agitation of 500 rpm for 180 min.…”
Section: Polymerization Reactionsmentioning
confidence: 99%
“…[8,9,14] The zeta potential values shown in Table 2 for particles prepared with the anionic surfactant SDS were negative, while zeta potential values were positive for particles prepared with the cationic surfactant CTAB, as expected, confirming that the surfactant is located at the particle surface. [8,16,[31][32][33][34] However, in all other cases, the zeta potential values were largely negative (with exception of PVA), indicating the enormous influence of KPS on the accumulation of charges in the surfaces that separate the organic and the aqueous phases. Although this effect has been emphasized in many previous investigations, [20,26,35] the fact is that the use of nonionic surfactants may be insufficient to reduce the zeta potential values of polymer particles, as required by modern regulations, if ionic initiators are not replaced by alternative biocompatible non-ionic initiators (such as benzoyl peroxide, BPO).…”
Section: Particles Produced By Sonifiermentioning
confidence: 99%
See 1 more Smart Citation